Prevalence of S. pneumoniae carriage among children organized in kindergarten groups in Khanty-Mansiysk city - A.A. Garina; F.I. Petrovski; Yu.A. Petrovskaya; A.L. Zaplatnikov (LCC «Medicine-Inform», 2023)
A.A. Girina1, F.I. Petrovsky1, Yu.A. Petrovskaya1, A.L. Zaplatnikov2 1Khanty-Mansiysk State Medical Academy, Khanty-Mansiysk, Russian Federation 2Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation Aim: to assess the landscape of pneumococcus serotypes among children organized in kindergarten groups in Khanty-Mansiysk city. Patients and Methods: the study included 510 children (2-6 years old) attending kindergartens in Khanty-Mansiysk city. The children were divided into 2 groups: vaccinated (n=50) and non-vaccinated against pneumococcal infection (n=460). The data on vaccination status were received from the prophylactic immunization records (Form 063/u) and child's medical records (Form 112/u). In addition, the following data were analysed: age, gender, gestation age at birth, attitudes of child's legal representatives towards vaccinations, and the presence of chronic health problems. Pneumococcal polysaccharide conjugate adsorbed 13-valent vaccine (PCV-13) was used for the prevention of pneumococcal disease. Nasopharyngeal swabs were collected from children as a source of biological material. The pneumococcus was detected using a culture-based method and PCR assay. Results: the average age of organized children examined in Khanty-Mansiysk for Streptococcus pneumoniae (S. pneumoniae, pneumococcus) was 54.31 [53.46-55.16] months. In 56% of the examined children, pneumococcal DNA was found in nasopharyngeal swabs by polymerase chain reaction assay. The identified serotypes in 71.1% of cases were the same as in the PCV13 vaccine formulation. The most common serotypes detected were 4 (27%), 19 F (13.3%), 23 F (3.6%) and serogroup 6 (11.6%). In children immunized against S. рneumoniae, the pneumococcal strain DNAs, same as the vaccine strain DNAs, were found in 53.7% of cases, while in non-immunized children - in 73% of cases (OR 0.54, 95% CI 0.29-0.97). Conclusion: the increasing prevalence of S. рneumoniae carriage in children as they get older and attend organized children's groups for a longer time, along with the predominance within the population of the same pneumococcus strains as those in the vaccine formulation, dictate the need for timely immunization against pneumococcal infection in compliance with the National Vaccination Schedule (vaccination at 2 and 4.5 months of age, revaccination at 15 months of age). Keywords: children, pneumococcal infection, S. pneumoniae, vaccination, pneumococcal conjugate vaccine, children in organized groups, carriage. For citation: Girina A.A., Petrovsky F.I., Petrovskaya Yu.A., Zaplatnikov A.L. Prevalence of S. pneumoniae carriage among children organized in kindergarten groups in Khanty-Mansiysk city. Russian Journal of Woman and Child Health. 2023;6(2):164-168 (in Russ.). DOI: 10.32364/2618-8430-2023-6-2-164-168.